Problem-based learning at Ahmad Ibrahim Kuliyyah of Laws and the inculcation of Islamic values - Mobarak Ali, Bashiran Begum; Mohamad, Nor Asiah (International Islamic University Malaysia, 2009)
Problem-based learning (PBL) serves as an alternative tool in the teaching of law at the International Islamic University Malaysia (IIUM). IIUM emphasises on producing well-rounded graduates who are professionally qualified and who practice Islamic values. Problem-based learning has proven to be a very effective complementary tool in achieving this educational aim. The main elements of problem-based learning (PBL) are the study of the real case problems, team work, time management, reflective journal writing and peer evaluation. All of these elements form essential parts of the Islamic education system. This paper discusses the Islamic values existing in problem-based learning and evaluates to what extent Ahmad Ibrahim Kuliyyah of Laws (AIKOL) in general, and the course Equity and Trust in particular, has succesfully harmonised and integrated problem-based learning with Islamic values.